2009
DOI: 10.1038/ng.311
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide scan reveals association of psoriasis with IL-23 and NF-κB pathways

Abstract: Psoriasis is a common immune mediated disorder that affects the skin, nails, and joints. To identify psoriasis susceptibility loci, we genotyped 438,670 SNPs in 1,409 European ancestry psoriasis cases and 1,436 controls. Twenty-one promising SNPs were followed-up in 5,048 psoriasis cases and 5,041 controls. Our results provide strong support for the association of at least seven genetic loci and psoriasis (each with p < 5×10−8 overall). Loci with confirmed association encode HLA-C, three genes involved in IL-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
1,156
7
25

Year Published

2009
2009
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,252 publications
(1,241 citation statements)
references
References 31 publications
28
1,156
7
25
Order By: Relevance
“…Recently, a genome-wide association scan fo 1,409 psoriasis patients and 1,436 controls revealed a strong association of psoriasis with single nucleotide polymorphisms in loci including ABIN-1 and A20 [68]. Moreover, this study also revealed altered expression of ABIN-1 in the skin of psoriasis patients, indicating that changes in the expression of ABIN-1 may be a key event in the initiation and progression of psoriasis.…”
Section: Abins In Diseasementioning
confidence: 53%
“…Recently, a genome-wide association scan fo 1,409 psoriasis patients and 1,436 controls revealed a strong association of psoriasis with single nucleotide polymorphisms in loci including ABIN-1 and A20 [68]. Moreover, this study also revealed altered expression of ABIN-1 in the skin of psoriasis patients, indicating that changes in the expression of ABIN-1 may be a key event in the initiation and progression of psoriasis.…”
Section: Abins In Diseasementioning
confidence: 53%
“…2 Genome-wide linkage scans have unambiguously mapped a primary disease susceptibility locus (PSORS1) to the major histocompatibility complex (MHC), 3 where refinement studies and resequencing efforts point to HLA-C as the most likely PSORS1 candidate. 4,5 More recently, the advent of genome-wide association scans has allowed the identification of several non-MHC susceptibility genes, including IL12B, IL23R, RNF114, TNFAIP3, TNIP1, IL4/IL13 and LCE3B/3C [6][7][8][9][10][11] Of these, IL12B and IL23R harbour variants that also confer susceptibility to Crohn's disease (CD) 12 and ankylosing spondylitis. 13 Similarly, TNFAIP3 alleles have been associated with rheumatoid arthritis, 14 systemic lupus erythematosus 15 and type I diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of these studies implicated different pathways; one highlighted the involvement of IL23 and nuclear factor-kB pathways, whereas the other study indicated the importance of epidermal differentiation process in the patho-physiology of psoriasis. 143,144 In any case, it is of merit to conduct GWAS in different populations for the same disease to examine the extent of population genetic heterogeneity.…”
Section: Extending Gwas To Different Populationsmentioning
confidence: 99%